As hipersuperfíces de Sbrana-Cartan - Bronzatti, Marinez (Universidade Federal de São Carlos, 2013)
In this work, based on the papers [5] and [6], we present the classification of Euclidean hypersurfaces that admit nontrivial isometric deformations, called Sbrana -Cartan hypersurfaces, by means of the Gauss parameterization.
Keywords: Matemática; Geometria; CIENCIAS EXATAS E DA TERRA::MATEMATICA